E-lecturing in Media and communication Sciences, a review of the concept and planning methods - boulaouidet, houria; bensahla, dounia (Journal of Social Sciences and Humanities, 2024)
The advent of online lectures corresponded with the rise and evolution of communication and information technology, particularly with the introduction of the Internet, which provided the process with competitive advantages based on the network's capabilities. With the outbreak of COVID-19 and its consequences for public life and human gathering, and after encountering challenges in face-to-face communication and traditional teaching methodes, e-learning arose strongly in university settings- the adoption of online lectures as an altenative technique at first, followed by a hybrid subsequently. As a result of these recent innovations, online lectures have gained popularity. This intervention investgates the nature of electronic lecturing and how to plan for it using theoretical foundations and personal experience in this sector, as we have been providing online lectures for four years..